Reporting Quality in Math Meta-Analyses for Students with or at Risk of Disabilities. (January 2022) - Nelson, Gena; Park, Soyoung; Brafford, Tasia; Heller, Nicole A.; Crawford, Angela R.; Drake, Kevallyn R.
Researchers and practitioners alike often look to meta-analyses to identify effective practices to use with students with disabilities. The number of meta-analyses in special education has also expanded in recent years. The purpose of this systematic review is to evaluate the quality of reporting in meta-analyses focused on mathematics interventions for students with or at risk of disabilities. We applied 53 quality indicators (QIs) across eight categories based on recommendations from Talbott et al. to 22 mathematics intervention meta-analyses published between 2000 and 2020. Overall, the meta-analyses met 61% of QIs and results indicated that meta-analyses most frequently met QIs related to providing a clear purpose (95%) and data analysis plan (77%), whereas meta-analyses typically met fewer QIs related to describing participants (39%) and explaining the abstract screening process (48%). We discuss the variation in quality indicator scores within and across the quality categories and provide recommendations for future researchers.